Sleep patterns and symptoms of anxiety and depression in patients with chronic pain Padrão do sono e sintomas de ansiedade e depressão em pacientes com dor crônica - Martha M.C. Castro; Carla Daltro (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Sleep disturbances and symptoms of anxiety and depression have been shown to be involved in the genesis and perpetuation of chronic pain. OBJECTIVE: To evaluate sleep patterns and the prevalence of symptoms of anxiety and depression in patients with chronic pain. METHOD: Four hundred consecutive patients referred to a chronic pain outpatient clinic were investigated using patient charts, the numerical Visual Analogue Scale for the evaluation of pain, the Hospital Anxiety and Depression scale and the Mini-Sleep Questionnaire. RESULTS: The mean age of patients was 45.6±11.4 years. The most frequent medical diagnosis was myofascial pain followed by neuropathic pain. The prevalence of symptoms of anxiety was 72.8%, depression 93% and altered sleep patterns 93%. CONCLUSION: This study revealed a high prevalence of symptoms of depression and anxiety and alterations in sleep patterns in patients with chronic pain, justifying investigation into these disturbances in this group of patients. CONTEXTO: Distúrbios do sono e sintomas de ansiedade e depressão tem sido vistos no envolvimento da origem e perpetuação da dor crônica. OBJETIVO:Avaliação do padrão do sono e da prevalência de sintomas de ansiedade e depressão em pacientes com dor crônica. MÉTODO: Quatrocentos pacientes de dor crônica atendidos consecutivamente na clínica foram investigados usando os seguintes instrumentos a Escala Visual Analógica para a avalição da dor, a Escala Hospitalar de Ansiedade e Depressão e o Mini-Sleep Questionnaire. RESULTADOS: A média de idade dos pacientes foi 45,6±11,4 anos. O diagnóstico mais frequente foi de dor miofascial seguido de dor neuropática. A prevalência de sintomas de ansiedade foi 72,8%, de depressão foi 61,5% e de alteração do sono 93%. CONCLUSÃO: Este estudo revela uma alta prevalência de sintomas de depressão e ansiedade e alterações no padrão do sono em pacientes com dor crônica, justificando a investigação destes distúrbios neste grupo de pacientes.